Harry Potter and the order of the phoenix - Rowling, J. K. (Arthur A. Levine Books, 2003)
When the government of the magic world and authorities at Hogwarts School of Witchcraft and Wizardry refuse to believe in the growing threat of a freshly revived Lord Voldemort, fifteen-year-old Harry Potter finds support from his loyal friends in facing the evil wizard and other new terrors.